1998
DOI: 10.2105/ajph.88.12.1761
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and hospital admissions in Sydney, Australia, 1990 to 1994.

Abstract: Recent reviews indicate that ambient air pollution has important short-term effects on human health.'3 A number of epidemiological studies indicate that these effects occur at levels below existing air quality guidelines.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 30 publications
9
74
0
4
Order By: Relevance
“…Previous studies have shown no consistent effects of PM 10 and PM 2.5 on asthma hospitalization. A study conducted in Sydney, Australia, from 1990 to 1994 (33) indicated no significant effects of fine particulate (~PM 2.0 ) on asthma hospitalization for both children and adults. Another study from Birmingham, England (2), where the maximum level of PM 10 (130.9 µg/m 3 ) exceeded the levels found in Toronto (Table 1) and Seattle (12) by over 30%, also showed no significant effect of PM 10 on asthma hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown no consistent effects of PM 10 and PM 2.5 on asthma hospitalization. A study conducted in Sydney, Australia, from 1990 to 1994 (33) indicated no significant effects of fine particulate (~PM 2.0 ) on asthma hospitalization for both children and adults. Another study from Birmingham, England (2), where the maximum level of PM 10 (130.9 µg/m 3 ) exceeded the levels found in Toronto (Table 1) and Seattle (12) by over 30%, also showed no significant effect of PM 10 on asthma hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…High ambient levels of air pollution have been linked to infant mortality and hospital admissions for cardiac, pulmonary, and cerebral vascular disease (Ponka & Virtanen, 1996;Morgan, Corbett, & Wlodarczyk, 1998;Morris, Naumara & Muasmghe, 1995). After adjusting for smoking (itself a major toxic pollutant responsible for increasing, widespread death and disability) and other risk factors, Dockery et al (1993) found a strong association between fine dust particulate air pollution and mortality from lung cancer and cardiopulmonary diseases.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Although the health effects of short-term PM exposures are not well understood, several recent studies have correlated disease symptoms with increased ambient short-term PM. Asthma symptoms have been associated with 1-and 8-h maximum PM 10 concentrations (Delfino et al, 1998), increased chronic obstructive pulmonary disease hospital admissions with 1-h fine particle concentrations (Morgan et al, 1998), and decreased heart rate variability in elderly subjects with 4-h mean PM 2.5 concentrations (Gold et al, 2000).…”
Section: Introductionmentioning
confidence: 99%